Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fimmu.2017.01554
|View full text |Cite
|
Sign up to set email alerts
|

Crystallizable Fragment Glycoengineering for Therapeutic Antibodies Development

Abstract: Monoclonal antibody (mAb)-based therapeutics are the fastest growing class of human pharmaceuticals. They are typically IgG1 molecules with N-glycans attached to the N297 residue on crystallizable fragment (Fc). Different Fc glycoforms impact their effector function, pharmacokinetics, stability, aggregation, safety, and immunogenicity. Fc glycoforms affect mAbs effector functions including antibody-dependent cell-mediated cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC) by modulating the Fc–FcγR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 136 publications
0
58
0
Order By: Relevance
“…These complex N-glycans contain a core heptasaccharide motif with 4 N-acetylglucosamine (GlcNAc) residues and 3 mannose residues in a biantennary arrangement. 8,149 Fucose may be added to the protein-proximal GlcNAc residue, bisecting GlcNAc may be added to the central mannose residue, galactose may be added to each terminal mannose residue, and sialic acid (N-acetylneuraminic acid in mammals or N-glycolylneuraminic acid in some nonhuman mammals) may be additionally added to these galactose residues. All these possibilities for individual glycans, combined with the potential for differential glycosylation on each heavy chain, allow for significant heterogeneity in otherwise similar molecules of antibody.…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These complex N-glycans contain a core heptasaccharide motif with 4 N-acetylglucosamine (GlcNAc) residues and 3 mannose residues in a biantennary arrangement. 8,149 Fucose may be added to the protein-proximal GlcNAc residue, bisecting GlcNAc may be added to the central mannose residue, galactose may be added to each terminal mannose residue, and sialic acid (N-acetylneuraminic acid in mammals or N-glycolylneuraminic acid in some nonhuman mammals) may be additionally added to these galactose residues. All these possibilities for individual glycans, combined with the potential for differential glycosylation on each heavy chain, allow for significant heterogeneity in otherwise similar molecules of antibody.…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…Common strategies to modify glycosylation in cell culture include the addition of glycan precursors to increase saccharide incorporation or glycosyltransferase inhibitors to decrease incorporation. 149,159 In addition, the genes for glycosylating enzymes within host cells may be knocked out to reduce fucosylation and nonhuman glycosylation or knocked in to provide a more human-like glycosylation profile. Clinical trials such as one with the Food and Drug Administrationeapproved obinutuzumab have demonstrated that low-fucose glycovariants from engineered cell lines may lower the risk of disease progression, but increase adverse events, compared with nonglycoengineered antibodies.…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…For example, margetuximab, developed by Mac-roGenics, had adapted the same Fab target (Her2) as transtuzumab but had been Fc-engineered to maximize immune effector function by elevating relative affinity to activating Fcγ receptor, FcγRIIIa over inhibitory Fcγ receptor, FcγRIIb, and it recently showed a 24% risk reduction in patients relative to that of trastuzumab in a phase 3 clinical trial in 536 breast cancer patients 69 . Other significant efforts have been directed to the engineering of antibodies with improved affinity for FcγRIIIa and enhanced effector function by amino acid mutations 36,[70][71][72][73][74] or glycan modifications [75][76][77][78][79][80][81] . Hatori and coworkers also engineered an antibody Fc variant (P238D/L328E) that showed selectively enhanced FcγRIIb binding over both FcγRIIa-R131 and FcγRIIa-H131 82 .…”
Section: Engineering Effector Functions Of Antibodiesmentioning
confidence: 99%
“…Gramer et al (2011) galactosylated species and, therefore, confirmed the possibility of obtaining high galactosylation levels in vitro. This may be overcome by protein engineering in the Fc region Li, Zhu, Chen, Feng, & Dimitrov, 2017). In addition, because Fc-glycans are rather protected in the Fc part of the antibody, enzymes might be sterically hindered from interacting with the glycans (Nigrovic, 2013).…”
Section: Galactosylation and Sialylationmentioning
confidence: 99%
“…In addition, because Fc-glycans are rather protected in the Fc part of the antibody, enzymes might be sterically hindered from interacting with the glycans (Nigrovic, 2013). This may be overcome by protein engineering in the Fc region Li, Zhu, Chen, Feng, & Dimitrov, 2017).…”
Section: Galactosylation and Sialylationmentioning
confidence: 99%